 # If x + y = - 6 and xy = 2.75, what is X-Y equal to

## If x + y = - 6 and xy = 2.75, what is X-Y equal to

(x+y) ²= (-6) ²
x ²+ y ²+ 2xy=36
x ²+ y ²= 36-2xy=30.5
(x-y) ²
=x ²+ y ²- 2xy
=30.5-5.5
=25
So X-Y = - 5 or 5

### There is such a question: "calculate the value of: (X-Y) [(x + y) ^ 2-xy] + (x + y) [(X-Y) ^ 2 + XY], where x = 2006 and y = 2008. Xiao Ming mistakenly copied y = 2008 as y = 2080, but he was right to calculate the result. Why?

(x-y)[(x+y)^2-xy]+(x+y)[(x-y)^2+xy]
=x^3-y^3+x^3+y^3
=2x^3
This value has nothing to do with y, so if you copy wrong y, the result will not be affected

x-0.6=0
y+3.75=0
x=0.6
y=-3.75
-xy
=-0.6*(-3.75)
=9/4

### (2x+3) × (3x-2) calculated by multiplication formula In fact, the original question is (x + y) (2x + y) - (x + 2Y) (x-2y)

It can be written as: 2x (3x-2) + 3 (3x-2) gets 6x ²- 4X+9X-6＝6X+5X-6

### Calculation: [(4x ^ 2-x ^ 3-2x) divided by 2x] - (x-1) ^ 2

solution
[(4x ²- x ³- 2x)÷2x]-(x-1) ²
=(2x-1/2x ²- 1)-(x ²- 2x+1)
=2x-1/2x ²- 1-x ²+ 2x-1
=(-1/2x ²- x ²)+ (2x+2x)+(-1-1)
=-3/2x ²+ 4x-2

### 2x-1 / 3 = - x + 2 / 3 how is it calculated to be transferred

Is your equation like this: 2x - (1 / 3) = - (x / 3) + 2
2x-1 / 3 = - x + 2 / 3
2X + X / 3 = 1 / 3 + 2
Simplified to 7x / 3 = 7 / 3
Solution: x = 1